Reply to Oppy on God, the Best and Evil - Langtry, Bruce (Sophia, 2011)
My reply corrects one misstatement in Oppy’s summary of my book, abandons a footnote in the light of one of Oppy’s criticisms, and argues that Oppy’s other criticisms do not succeed in showing either that my claims are mistaken or that the arguments by which I supported them are defective.